2014
DOI: 10.1210/en.2013-1960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroid Hormone on Bone Mass, Bone Strength, and Bone Regeneration in Male Rats With Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is associated with increased skeletal fragility and impaired fracture healing. Intermittent PTH therapy increases bone strength; however, its skeletal and metabolic effects in diabetes are unclear. We assessed whether PTH improves skeletal and metabolic function in rats with T2DM. Subcritical femoral defects were created in diabetic fa/fa and nondiabetic +/+ Zucker Diabetic Fatty (ZDF) rats and internally stabilized. Vehicle or 75 μg/kg/d PTH(1-84) was sc administered over 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 29 publications
5
69
1
1
Order By: Relevance
“…PTH had no effect on body weight, glucose tolerance or pancreatic islet morphology in both groups, despite PTH therapy resulting in bone anabolic effects and bone defect repair. Unfortunately, the authors were unable to detect undercarboxylated OC; however, they reported no change in carboxylated OC between vehicle and PTH-treated non-diabetic and diabetic rats (Hamann et al 2014). These results are surprising as intermittent therapy is known to increase serum levels of OC (Neer et al 2001, Greenspan et al 2007.…”
Section: Fracture Burden and Global Energy Metabolismmentioning
confidence: 93%
“…PTH had no effect on body weight, glucose tolerance or pancreatic islet morphology in both groups, despite PTH therapy resulting in bone anabolic effects and bone defect repair. Unfortunately, the authors were unable to detect undercarboxylated OC; however, they reported no change in carboxylated OC between vehicle and PTH-treated non-diabetic and diabetic rats (Hamann et al 2014). These results are surprising as intermittent therapy is known to increase serum levels of OC (Neer et al 2001, Greenspan et al 2007.…”
Section: Fracture Burden and Global Energy Metabolismmentioning
confidence: 93%
“…on the other hand a recent animal study by Hamann et al (37), shows no effect of iPTH on rat body weight.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies show that uOC influences β cells proliferation and activity (2,21,22), whereas others do not (37).…”
Section: Discussionmentioning
confidence: 99%
“…6 The scan region ranges between 0.1 and0.7 mm for both mice and rats. 2,11,[14][15][16] If using a percentage of the long bone length, 10-15% of the total length is common. 6,17 In this case, it is recommended to scan a larger region than needed and to calculate a subregion in the analysis phase.…”
Section: Scanning Proceduresmentioning
confidence: 99%
“…The majority of studies on the vertebra examine the entire vertebral body. 11,14,15,19,20 Alternatively, some researchers have specified a volume (for example, 2 mm) centred at the midline, 8 or they have used the growth plate as a landmark. 7,21,22 As the mid-region is sparsely populated with trabecular bone, and the bone volume density is inhomogeneously distributed throughout the vertebral body, it is recommended to analyse the entire volume unless the study question gives cause to focus on a specific subvolume.…”
Section: Trabecular Bonementioning
confidence: 99%